Formulation and Evaluation of Wrightia tinctoria Emulgel for the Treatment of Psoriasis (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: Psoriasis can be a debilitating condition, but there may be a solution. Recently, several studied showedthat emulsion-based topical drug delivery system could be a promising approach for the treatment of psoriasis.Hence, in the present study, Wrightia tinctoria (WT) oil-based emulgel was developed for the enhancement ofeffectiveness against psoriasis. Materials and Methods: This breakthrough treatment could be an alternativetechnique for the management of psoriasis. WT oil was used to prepare emulsions, which was loaded into a gelbase. The concentration different excipients varied to prepare various emulsion formulations and evaluated fordifferent parameters. The developed formulations were evaluated for the various parameters such as drug content,particle size, zeta potential, viscosity, pH and percentage drug release. Results and Discussion: The optimizedformulation (F4) was found to have droplet size of 3218 ± 1.24 nm, 0.0175 ± 1.78 V zeta potential, entrapmentefficiency of 59.53 ± 8.42%, and spreadability of 2.901 ± 0.12 mm. The pH and viscosity of optimized WT oil-basedemulgel was found to be 6.1 ± 0.578 and 94,374 ± 198 cp, respectively. In vitro release of WT oil from optimizedemulgel was found to be 98.87 ± 1.15% in 10 h. In 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromidecytotoxicity study indicated no significant difference between the WT oil and its emulgel. Thus, suggested noloss of anti-proliferation activity of WT oil on formulation in emulgel. Conclusion: This study showed that theemulgel formulation has the potential to significantly enhance the efficacy of WT oil in treating psoriasis. Thesefindings provide exciting new possibilities for improving psoriasis treatment and highlight the importance ofcontinued research in this area.